2013
DOI: 10.1093/brain/awt283
|View full text |Cite
|
Sign up to set email alerts
|

SIL1 mutations and clinical spectrum in patients with Marinesco-Sjögren syndrome

Abstract: Marinesco-Sjögren syndrome is a rare autosomal recessive multisystem disorder featuring cerebellar ataxia, early-onset cataracts, chronic myopathy, variable intellectual disability and delayed motor development. More recently, mutations in the SIL1 gene, which encodes an endoplasmic reticulum resident co-chaperone, were identified as the main cause of Marinesco-Sjögren syndrome. Here we describe the results of SIL1 mutation analysis in 62 patients presenting with early-onset ataxia, cataracts and myopathy or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
89
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 40 publications
4
89
1
Order By: Relevance
“…Skeletal muscle weakness is also a prominent characteristic. Almost all the MSS patients with SIL1 mutations in this series had muscle weakness initially noticed as a delayed motor milestone, which was detected at an earlier age than cataracts, as reported previously [3,15,16]. Regarding muscle biopsy, myopathic changes, including RV formation are a characteristic of patients with SIL1 mutations.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Skeletal muscle weakness is also a prominent characteristic. Almost all the MSS patients with SIL1 mutations in this series had muscle weakness initially noticed as a delayed motor milestone, which was detected at an earlier age than cataracts, as reported previously [3,15,16]. Regarding muscle biopsy, myopathic changes, including RV formation are a characteristic of patients with SIL1 mutations.…”
Section: Discussionsupporting
confidence: 79%
“…We could not exclude the possibility of the mutation occurred in the promoter or other non-coding region of SIL1 in these 3 patients. Previous reports also showed that approximately one-half of the MSS patients were genetically diagnosed as MSS from mutations in SIL1 [7,16]. The absence of RVs in the muscle biopsy tissue of one patient with no SIL1 mutation suggests the existence of a different disease mechanism(s) in such patients.…”
Section: Discussionmentioning
confidence: 84%
“…In humans, mutations in the SIL1 gene have been found in over half the cases of M arinesco- S jögren s yndrome (MSS) 152154 an autosomal recessive disease characterized by multisystem defects including cerebellar ataxia due to Purkinje cell loss, progressive myopathy, early onset cataracts, skeletal abnormalities, and a variety of developmental abnormalities and intellectual disabilities 155158 . MSS-associated mutations occur throughout the SIL1 gene and most lead to the disruption of significant portions of the protein 98; 153; 155 , including those regions that interact with BiP.…”
Section: Contribution Of Er Nefs To Biological Functionsmentioning
confidence: 99%
“…6,7 Marinesco-Sjögren syndrome (MSS [MIM:248800]) is a form of myopathy with a similar constellation of findings including muscle involvement, intellectual disability, cataracts, brain MRI findings, and other signs of central nervous system (CNS) involvement. 8,9 Cerebellar atrophy is often considered the most prominent neuroradiologic finding in MSS, but it is not an obligatory finding. 10 The clinical overlap can therefore make it difficult to distinguish between syndromic CMDs and MSS.…”
mentioning
confidence: 99%